ПЕДАГОГІЧНА АНТРОПОЛОГІЯ – РУШІЙ ЕВОЛЮЦІЇ ВІТЧИЗНЯНИХ ПЕДАГОГО-ЕКСПЕРИМЕНТАЛЬНИХ ДОСЛІДЖЕНЬ (ОСТ. ТРЕТИНА ХІХ – ПОЧАТОК ХХ СТ.) - Dichek, N (Continuing Professional Education: Theory and Practice, 2019)
The connection between the theoretically proclaimed demands to the child`s all-round study and their specifi cally scientifi c realizations by means of the experimental researches that have been conducted at the beginning stage of the domestic pedagogic anthropology development is defi ned in the article; the main components of the I. Sikorskiy`s and O. Lazurskiy`s scientifi c heritages are analyzed; the necessity to make reconstruction and reproduction of the national history of pedagogy true development is emphasized